Thin Films for Energy Harvesting, Conversion, and Storage - Zhao, Xin (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Efficient clean energy harvesting, conversion, and storage technologies are of immense importance for the sustainable development of human society. To this end, scientists have made significant advances in recent years regarding new materials and devices for improving the energy conversion efficiency for photovoltaics, thermoelectric generation, photoelectrochemical/electrolytic hydrogen generation, and rechargeable metal ion batteries. The aim of this Special Issue is to provide a platform for research scientists and engineers in these areas to demonstrate and exchange their latest research findings. This thematic topic undoubtedly represents an extremely important technological direction, covering materials processing, characterization, simulation, and performance evaluation of thin films used in energy harvesting, conversion, and storage.